Predictors of poor glycemic control in type 2 diabetic patients in South Indian population - De, Pushpita; Banu, Shaheen; Muthukumar, Diviya (International Journal of Research in Medical Sciences, 2018)
Background: The aim of this study is to shed light on the patients ‘knowledge, expectations and attitudes with regards to glucose control, and to understand the barriers to achieving good glucose control among south Indian patients with type 2 diabetes. Methods: A cross-sectional study was conducted among 76 type 2 diabetic patients in this study. Patients’ information such as sociodemographic characteristics, family history of diabetes, diabetes duration, medication adherence, dietary pattern, physical activity was obtained through interview. Anthropometric details were noted during the interview. All available last readings for fasting blood sugar, post prandial blood sugar and glycosylated hemoglobin were abstracted from patients’ records. Results: A total of 76 patients were enrolled in the study. The overall mean (SD) duration of the disease was 9±7.02 years. 63% had HbA1c ≥7%, which is categorized as a poor glycemic control. 43% of the subjects had poor glucose control who did not follow healthy eating plans. 84% of the patients did participate in physical exercise but did not follow as recommended. 67% of the patients have poor knowledge about glucose control. Conclusions: The main results indicate that glycemic control in type 2 diabetes is generally poor. Longer duration of diabetes and not adherent to diabetes self-care management behaviors were associated with poor glycemic control. Therefore, a balanced approach to improve awareness about diabetes and its control both among patients and the medical fraternity is urgent need of the hour in India.